Strategi pemasaran dalam membangun brand awareness produk Camille Beauty melalui platform Tiktok - Permana, Erwin; Ahyani , Syafira; Ramadhanti , Diah; Ananda , Diva (ARKA INSTITUTE, 2023)
The cosmetic industry in Indonesia has grown very rapidly from year to year with various brands, both imported and local. One local brand that is growing rapidly is Camille Beauty. One of the factors that has boosted the popularity of Camille Beauty products is the marketing carried out using the tiktok platform. This study aims to analyze marketing strategies in building brand awareness for Camille Beauty products through the TikTok platform. This study uses a qualitative approach. The research data uses secondary data. The data was obtained from searches on various official and popular sites as well as various scientific publications. Data is presented by using descriptive data analysis techniques. The results of the study show that there are several marketing strategies in building brand awareness for Camille Beauty products through the TikTok platform, namely first, Camille Beauty creates creative and interesting content; second, implementing the use of hashtags that are relevant to their products and the beauty industry in general; third, using the live feature on TikTok which really helps Camille Beauty in promoting its products directly through online networks; Fourth, give discounts. It can be concluded that Camille Beauty has implemented its marketing strategy appropriately and in accordance with its targets.